1990
DOI: 10.1161/01.atv.10.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Uremic levels of oxalic acid suppress replication and migration of human endothelial cells.

Abstract: Patients with chronic renal failure who undergo hemodlalysis experience accelerated atherosclerosis and premature death. Since the end-metabolite, oxalic acid, accumulates In plasma In proportion to the severity of renal failure, we studied whether sodium oxalate (0 to 300 /tM) Is an endothellal toxin and, therefore, might enhance atherogenesls. Exposure to uremic levels of oxalate (>30 /JM) for 9 to 28 days depressed endothelial cell replication by 33% to 84% (mean±SD, 54%±15.7%, n=17 experiments, p=0.002.). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Our data in conjunction with past observations suggest that, if calcium oxalate precipitates are formed during the interdialytic period, such precipitates may dissolve post-HD and oxalosis does not ensue, as long as the post-HD P[Ox] is b30 μM. Ox could still be a uremic toxin [32,33] that might exert deleterious effects outside the pathway of crystal deposition [34]. However, such effects may not occur until P[Ox] is sustained above 30 μM [34].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our data in conjunction with past observations suggest that, if calcium oxalate precipitates are formed during the interdialytic period, such precipitates may dissolve post-HD and oxalosis does not ensue, as long as the post-HD P[Ox] is b30 μM. Ox could still be a uremic toxin [32,33] that might exert deleterious effects outside the pathway of crystal deposition [34]. However, such effects may not occur until P[Ox] is sustained above 30 μM [34].…”
Section: Discussionsupporting
confidence: 76%
“…Ox could still be a uremic toxin [32,33] that might exert deleterious effects outside the pathway of crystal deposition [34]. However, such effects may not occur until P[Ox] is sustained above 30 μM [34]. Based on our data, levels in this range are now less commonly seen in HD patients, but may be more common in patients with advanced CKD not on dialysis [12].…”
Section: Discussionmentioning
confidence: 97%
“…Calcium oxalate deposition was reported in atherosclerotic lesions of coronary arteries and alterations in endothelial cell function were documented in correlation with plasma oxalate. 21,22 Also, uremic levels of oxalate suppress human endothelial cell replication and migration. 23 When treated with crystals, cultured endothelial cells induce superoxide anion production, indicating the role of oxidative stress on endothelial dysfunction induced by hyperoxaluria.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the relationship between the colon and the kidneys may also influence cardiovascular outcomes in the HD patient population. In this regard, Levin et al [23] investigated whether oxalic acid has toxic effects on the endothelium. These authors concluded that oxalic acid, because it is a uremic toxin, may inhibit endothelial cell function, replication, and migration.…”
Section: Discussionmentioning
confidence: 99%